2003
DOI: 10.1074/jbc.m301105200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Monomeric Escherichia coli Alkaline Phosphatase Formed upon a Single Amino Acid Substitution

Abstract: Alkaline phosphatase (AP) from Escherichia coli as well as APs from many other organisms exist in a dimeric quaternary structure. Each monomer contains an active site located 32 Å away from the active site in the second subunit. Indirect evidence has previously suggested that the monomeric form of AP is inactive. Molecular modeling studies indicated that destabilization of the dimeric interface should occur if Thr-59, located near the 2-fold axis of symmetry, were replaced by a sterically large and charged res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
55
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 34 publications
0
55
1
Order By: Relevance
“…1D). The substitution of charged residues, such as Asp, Arg, and Glu into a protein dimer or oligomer interface has been shown to be a viable approach for preparing monomeric enzymes (25,(37)(38)(39).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1D). The substitution of charged residues, such as Asp, Arg, and Glu into a protein dimer or oligomer interface has been shown to be a viable approach for preparing monomeric enzymes (25,(37)(38)(39).…”
Section: Resultsmentioning
confidence: 99%
“…X-ray crystal structure and size exclusion chromatography analyses have revealed that hHint1 exists as a homodimer (2,23,24). Similar to other homodimeric enzymes, such as bacterial alkaline phosphatase, each monomer contains a well separated active site that does not participate in the dimer interface (25). Nevertheless, the C terminus of each monomer does form a range of contacts with the adjacent monomer in close proximity to the active site.…”
mentioning
confidence: 99%
“…Although ERGIC-53 and Emp47p oligomerization is important for ER export, it is less clear how oligomerization influences cargo interaction (34,35). Erv26p was shown previously to form homo-oligomers (36), and ALP is known to assemble into functional homodimers in yeast (37) as well as in other species (38). To probe the arrangement of the Erv26p homo-oligomer, chemical cross-linking followed by polyacrylamide gel analysis was used to determine the size of any cross-linked species.…”
Section: Erv26pmentioning
confidence: 99%
“…Previous work on EAP showed that the introduction of amino acids with large, bulky, and charged side chains into the interface of EAP disturbs the formation of the dimeric structure. The replacement of Thr59 with Arg resulted in the formation of a monomeric EAP mutant with little activity, and in B. subtilis APIV, a monomeric PhoA, the corresponding residue is also Arg [53]. Amino acid align ments showed that the residue in AP A , which corresponds to Thr59 in EAP, is also an Arg.…”
Section: Discussionmentioning
confidence: 99%